Exploring the Effects of Argument Map-Supported Online Group Debate Activities on College Students’ Critical Thinking - Chen, Xinya; Wang, Li; Zhai, Xuesong; Li, Yan (Frontiers in Psychology, 2022)
Debate has been warranted as a meaningful activity to promote students’ higher-level thinking, such as critical thinking. However, traditional debate activities that are typically carried out in the physical classroom may meet some obstructions of limited time and space, which would result in the phenomenon that many participants act as silent watchers rather than mind exchangers. Moreover, it is hard to make a visualized record about the whole process and contents of the traditional debate activity. The current study aimed to explore the effects of argument map (AM)-supported online group debate activities on college students’ critical thinking, including their depth and phases of critical thinking, and the relationship between students’ depth of critical thinking and their number of speeches. 42 sophomores in the undergraduate course named “Learning Sciences and Technology” were recruited to attend online group debate activities assisted by a web-based visualization tool named “ZJU Yuque” in five weeks. Newman’s framework about the depth of critical thinking and Murthy’s instrument of critical thinking phases were employed as guidelines. We found that 42 students’ overall depth of critical thinking were gradually improved in an obvious way during the five online debate activities. The most frequently phases for students in the first and second team in online group debate activities include Understand→Understand (U→U), Recognize→Understand (R→U), and Understand→Evaluate (U→E). However, students’ creating behaviors were not significantly generated. Teachers’ real-time feedback was helpful for students’ improvements of high-level thinking skills and their preparation for next debate activity. Student interview found that students highly valued such online group debate activities because every student could have chance to express their thoughts and they had enough time to prepare debate contents. Based on the findings, some implications were proposed for the better design and implementation of online group debate activities.